Flexible bronchoscopy and mechanical ventilation in managing Mounier-Kuhn syndrome: a case report - Kaya, Aslihan Gürün; Çiledağ, Aydin; Atasoy, Çetin; Karnak, Demet (São Paulo Medical Journal, 2018)
CONTEXT: Mounier-Kuhn syndrome is a rare congenital condition with distinct dilatation and diverticulation of the tracheal wall. The symptoms may vary and the treatment usually consists of support. CASE REPORT: The patient was a 60-year-old male with recurrent hospital admission. He was admitted in this case due to dyspnea, cough and sputum production. An arterial blood sample revealed decompensated respiratory acidosis with moderate hypoxemia. A chest computed tomography (CT) scan showed dilatation of the trachea and bronchi, tracheal diverticula and bronchiectasis. Flexible bronchoscopy was performed, which revealed enlarged airways with expiratory collapse. Furthermore, orifices of tracheal diverticulosis were also detected. Non-invasive positive pressure ventilation (NPPV) was added, along with long-term oxygen therapy. At control visits, the patient’s clinical and laboratory findings were found to have improved. CONCLUSION: Flexible bronchoscopy can be advocated for establishing the diagnosis and non-invasive mechanical ventilation can be used with a high success rate, for clinical wellbeing in Mounier-Kuhn syndrome.